AVLONIYNING “MUXTASAR TARIXI ANBIYO VA TARIXI ISLOM” ASARIDA YOSHLARNI DINIY QADRIYATLARGA HURMAT RUHIDA TARBIYALASH MASALALARI (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article, in Awlani's work "Brief history of history and history of Islam", the main goal is to mobilize the energy of young people to build an enlightened society that the future generations want to build. intended. Awlani's "A Brief History of Islam" revealed that enlightenment is a "matter of life and death" for humanity.